2021
DOI: 10.1038/s41409-021-01512-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel device for cryoprevention of oral mucositis: a randomized, blinded, multicenter, parallel group, phase 3 trial

Abstract: Cryoprevention (CP) using ice (IC) is an effective strategy to prevent chemotherapy-induced oral mucositis (OM). However, the use of IC may cause adverse reactions and requires water of safe quality to minimize risk of serious infections. This randomized, blinded, parallel group, phase 3 trial was conducted in five Scandinavian centers. Eligible patients were diagnosed with multiple myeloma or lymphoma, scheduled to receive conditioning with high-dose chemotherapy prior to autologous hematopoietic stem cell tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Further, the ICD proved to enhance the e cacy of conventional IC in prevention of OM in patients with lymphoma, whereas e cacy results were comparable between the two cooling methods in the myeloma group. The collective tolerability data were in accordance with the previous study in healthy volunteers [19]. It was also shown that cooling with the ICD 15°C was better tolerated than the ICD 8°C but displayed inferior capacity in temperature reduction [28].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Further, the ICD proved to enhance the e cacy of conventional IC in prevention of OM in patients with lymphoma, whereas e cacy results were comparable between the two cooling methods in the myeloma group. The collective tolerability data were in accordance with the previous study in healthy volunteers [19]. It was also shown that cooling with the ICD 15°C was better tolerated than the ICD 8°C but displayed inferior capacity in temperature reduction [28].…”
Section: Discussionsupporting
confidence: 88%
“…Until recently, when a novel intraoral cooling device (ICD) was introduced, only modest resources had been devoted to further develop the modality of cooling in conjunction with chemotherapy. This is somewhat surprising since the superiority of OC for prevention of chemotherapy-induced oral mucositis (OM) has been demonstrated in several trials [16,19,26,27]. Cooling with the ICD was equally effective but better tolerated when compared to ice chips (IC) in healthy volunteers [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with existing evidence, the results of the present study confirm that CT is an effective strategy to prevent the events which may precede clinically established OM. Furthermore, suggesting that cooling at higher temperatures, e.g., using cooling devices that can operate at higher temperatures [ 12 , 14 ], may be advantageous in clinical settings to prevent chemotherapy-induced OM.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this pertains to early events that precede clinically established OM. Cryotherapy (CT), i.e., the use of ice or cooling devices to cool the oral mucosa, continues to have considerable promise in clinical settings to reduce chemotherapy-induced OM [8][9][10][11][12]. However, while CT effectively alleviates OM in patients receiving chemotherapy, the knowledge is scarce regarding the ideal temperature for prevention of OM.…”
Section: Introductionmentioning
confidence: 99%